The fabrication of a supra-amphiphile for dissipative self-assembly. Issue 2 (16th November 2015) - Wang, Guangtong; Tang, Bohan; Liu, Yang; Gao, Qingyu; Wang, Zhiqiang; Zhang, Xi
Abstract : Dissipative self-assembly is a challenging but attractive field of supramolecular science, because it generally concerns complex system but is more close to the self-assembly of living bodies. We successfully realized dissipative self-assembly by coupling a supra-amphiphile with a chemical oscillator. Abstract : Dissipative self-assembly is a challenging but attractive field of supramolecular science, because it generally concerns complex systems but is more close to the self-assembly of living bodies. In this article, we realized dissipative self-assembly by coupling a supra-amphiphile with a chemical oscillator. The supra-amphiphile was fabricated with iodine and a double hydrophilic block copolymer containing PEG segments, as the non-covalent interaction between PEG and iodine could turn PEG hydrophobic, leading to the formation of the supra-amphiphile. The self-assembly and disassembly of the supra-amphiphile could be controlled by varying the concentration of iodine. Therefore, the dissipative self-assembly of the supra-amphiphile was realized when it was coupled with the IO3 − –NH3 OH + –OH − chemical oscillator, which was able to produce iodine periodically. Meanwhile, the kinetic data of the self-assembly and disassembly of the supra-amphiphile could be estimated by the theoretical simulation of the chemical oscillations. This line of research promotes the self-assembly of supra-amphiphiles one step forward from thermodynamic statics to a dissipative system, and also suggests a new strategy to investigate the kinetics of stimuli-responsive molecular self-assembly.